2016
DOI: 10.1097/ajp.0000000000000230
|View full text |Cite
|
Sign up to set email alerts
|

Digital Pain Drawings

Abstract: Pain drawings recorded with touch-screen technology provide equal reliability to paper but the size of the drawing slightly differs between the platforms. Although, 2D line drawings and 3D body schemas were similar in terms of consistency and reliability, it remains to be confirmed whether 3D body schemas increase the accuracy and precision of pain drawings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Body charts using different 3D techniques, such as contoured sketches [26], photographs [27], and 3D illustrations or body charts [28-35] have been developed, and are generally preferred by patients [31,35]. This study showed that the preference for 2D versus 3D body charts was dichotomous, meaning that 50% of participants preferred the 3D and 40% preferred the 2D (10% did not have a preference).…”
Section: Discussionmentioning
confidence: 99%
“…Body charts using different 3D techniques, such as contoured sketches [26], photographs [27], and 3D illustrations or body charts [28-35] have been developed, and are generally preferred by patients [31,35]. This study showed that the preference for 2D versus 3D body charts was dichotomous, meaning that 50% of participants preferred the 3D and 40% preferred the 2D (10% did not have a preference).…”
Section: Discussionmentioning
confidence: 99%
“…corresponding to the individual peak pain level), the subjects marked the area of perceived pain on a digital generalized armchart using a 10.1" Samsung Note tablet (Samsung Electronics, South Korea) equipped with Navigate Pain software version 1.9.1 (Aalborg University, Aalborg, Denmark) for further analysis of the spatial pain profile. 9 The subjects were instructed to draw the area from which pain was sensed irrespective of area of redness, innocuous sensations such as warmth and the knowledge of the location of the application pad. The area of pain was later calculated with Navigate Pain as a percentage of the total chart area.…”
Section: Perceived Area Of Painmentioning
confidence: 99%
“…With the introduction of touch-screen technology, patientreported pain drawings can now be acquired with digital applications or drawing platforms as displayed on smartphones and personal computer tablets. These digital applications serve as reliable equivalents to paper-based pain drawings [1,2,10], with added and foreseeable future advantages. in the same way, digital pain drawings provide information about the number of pain sites and pain location.…”
Section: Moving Forward With Digital Technologiesmentioning
confidence: 99%
“…The revival of pain drawings as digital body maps for visualizing pain [1][2][3][4][5] and discomfort changes the way we understand patients and communicate with them [1]. A review of the literature following the introduction of pain drawings suggests that little information about a patient's condition can be extracted from the pain drawing alone.…”
Section: Introductionmentioning
confidence: 99%